О совпадении экспериментальных и расчетных данных по определению забойной мощности при бурении однослойными алмазными коронками - Кожевников, А.А.; Гошовский, С.В.; Дреус, А.Ю.; Мартыненко, И.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
In article the estimation of adequacy of a known equation for calculation of drilling power by comparison to experimental results is executed. Results of the analysis show a divergence of the experimental and theoretical data. The reasons of such mismatch are stated and problems of the further researches are defined.